The Development of Mental Health Learning Materials Using The Metacognitive Approach in Counseling Guidance Study Programme in FKIP UMSU - Jamilah, Jamilah; Haryati, Feri; Wastuti, Sri Ngayomi Yudha (International Journal for Educational and Vocational Studies, 2019)
This research aims to develop learning  materials for  mental health which be designed by Metacognitive approach. The development  model of  learning materials using Research and Development (R & D) methods who be developed by Borg and Gall and be combined with teaching development model Dick and Carey. The population for the product trials are UMSU students majoring in counseling guidance study programme. The instrument which be used is questionnaire . This products trials have three steps including personal gruops, small gruops and the field. Before products trials, the researcher does the expert validation trial for the content and design of learning materials for mental health using questionnaires according to the indicators that have been determined. Then the questionnaire be analysed to see the percentage and the validation criteria of Learning materials. The results of this research is a mental health diktat be designed used metacognitive approach.